Penerapan Model Pembelajaran Problem Based Learning dalam Membentuk Konsep Berpikir Peserta Didik - Arselina Heinan Arrul; Fuji Yuliani; Gusmaneli (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2024)
This research is motivated by problems that include the lack of student activeness, teachers still use methods that make students passive in learning, lack of enthusiasm for learning, and teachers do not stimulate students' critical thinking patterns during learning. The purpose of this research is to examine the application of learning-based learning models in schools. The method used is a literature study method from articles about the effect of problem-based learning models on students' thinking concepts. Based on the results of this study, it is found in these journals that the application of problem-based learning models can improve students' mindset and stimulate students to think critically and actively in learning. Based on the review of the articles, the application of the problem-based learning model is carried out during the learning process by giving examples of problems to students and providing opportunities for students to express their opinions.